Role of tumor cell surface lysosome-associated membrane protein-1 (LAMP1) and its associated carbohydrates in lung metastasis - Agarwal, Akhil Kumar; Srinivasan, Nithya; Godbole, Rashmi K.; More, Shyam K.; Budnar, Srikanth; Gude, Rajiv P.; Kalraiya, Rajiv D. (Journal of Cancer Research and Clinical Oncology, 2015)
Expression of lysosome-associated membrane protein-1 (LAMP1) on the surface correlates with metastatic potential of B16 melanoma cells. Downregulation of their expression in high metastatic (B16F10) cells reduced their surface expression and metastatic potential. Present investigations explore if overexpression of LAMP1 on the surface of low metastatic (B16F1) cells augment their metastatic ability, and if so, how? B16F1 cells were transduced with lentiviral vector carrying mutant-LAMP1 (Y386A) (mutLAMP1). Surface expression of LAMP1 and carbohydrates was analyzed by flow cytometry, immunofluorescence and/or immunoprecipitation and Western blotting. Cell spreading and motility were assessed on components of extracellular matrix (ECM) (fibronectin) and basement membrane (BM) (matrigel), and galectin-3-coated coverslips/plates. Metastatic potential was assessed using experimental metastasis assay. Pre-incubation with anti-LAMP1 antibodies significantly reduced lung metastasis of B16F10 cells. Overexpression of mutLAMP1 significantly increased its surface expression on B16F1 cells, resulting in increased cellular spreading and motility on fibronectin and matrigel. LAMP1 is the major carrier of poly-N-acetyllactosamine (polyLacNAc) on B16F10 cells. However, significantly higher expression of mutLAMP1 had no effect on galectin-3 binding on cell surface or on spreading or motility of cells on galectin-3-coated coverslips/plates. These cells also failed to show any gain in metastatic ability. This could be because LAMP1 from these cells carried significantly lower levels of polyLacNAc in comparison with B16F10 cells. PolyLacNAc on B16F10 cells and galectin-3 on lungs are the major participants in melanoma metastasis. Although surface LAMP1 promotes interactions with organ ECM and BM, carbohydrates on LAMP1 play a decisive role in dictating lung metastasis.
Keywords: 6 branched N-oligosaccharides; beta 1; Cell surface LAMP1; Galectin-3; Motility; Organ-specific metastasis; Poly-N-acetyllactosamine

Mass spectrometry based identification of galectin-3 interacting proteins potentially involved in lung melanoma metastasis - Dange, Manohar C.; Bhonsle, Hemangi S.; Godbole, Rashmi K.; More, Shyam K.; Bane, Sanjay M.; Kulkarni, Mahesh J.; Kalraiya, Rajiv D. (Molecular Biosystems, 2017)
Adhesive interactions between molecules on tumor cells and those on target organs play a key role in organ specific metastasis. Poly-N-acetyl-lactosamine (polyLacNAc) substituted N-oligosaccharides on melanoma cell surface glycoproteins promote lung specific metastasis via galectin-3 by facilitating their arrest and extravasation. This study reports the identification and characterization of galectin-3 interacting proteins using a combination of galectin-3 sepharose affinity and leucoagglutinating phytohemagglutinin (L-PHA) columns. A total of 83 proteins were identified as galectin-3 interacting glycoproteins, of which 35 were constituents of the L-PHA bound fraction, suggesting that these proteins carry polyLacNAc substituted beta 1,6 branched N-glycans. The identities of some of these proteins, like LAMP-1, LAMP-3, basigin, embigin, and alpha 5 and beta 1 Integrin, have been confirmed by western blotting, and functional relevance with respect to metastatic properties has been established.